Evaluation of training, patient and practitioner perspectives on community‐based monitoring of patients with stable age‐related macular degeneration compared to hospital‐based care: The FENETRE study report no. 1. (25th May 2021) - Read, Simon; Lawrenson, John G; Harper, Robert A; Hanley, Thomas; Balaskas, Konstantinos; Waterman, Heather
Abstract: Purpose: Describe the development, delivery, acceptability and evaluation of a modular training programme for community‐based, non‐medical practitioners monitoring patients with quiescent neovascular age related macular degeneration (QnAMD). Also, report on a qualitative process evaluation conducted during the pilot phase of a randomised control trial (the FENETRE Study) exploring patient and practitioner acceptability of community‐based QnAMD care relative to hospital‐based care. Methods: Learning outcomes from The College of Optometrists' Medical Retina higher qualifications and the Royal College of Ophthalmologists' Common Clinical Competency Framework were used to develop a competency framework for QnAMD care. Training was delivered online, comprising six asynchronous lectures followed by two synchronous case‐based discussion webinars, with an accredited assessment of 24 case vignettes. An anonymous evaluation survey was conducted with the first two FENETRE cohorts ( n = 38). Separately, we undertook a qualitative process evaluation, sampling purposively in four hospitals and five community‐based practices, interviewing nine patients and eight practitioners. Results: Survey responses ( n = 26) showed community optometrists were very satisfied ( n = 12; 46%) or satisfied ( n = 14; 54%) with the training; feedback reflected by qualitative process evaluation data. Overall, optometrists also felt either confident ( n = 15; 58%) or very confident ( n = 8; 31%) in conducting AMD monitoring appointments following training, a finding also corroborated by interview data from optometrists participating in the initial pilot phase roll‐out. Optometrists identified patient convenience and alleviating pressures in hospital care as the primary reasons for acceptability of community pathways. Data from patients entering community practices suggested they largely found this at least as safe and convenient as hospital care, although some patients randomised to hospital care perceived that as safer. Conclusion: This pilot study has shown the development and implementation of a collaborative community monitoring model is feasible, with satisfaction from community optometrists for training and accreditation, and broad acceptance for the pathway by both patients and practitioners.